Optimization of the block foundations - Chi, Tran; Dembicki, Eugeniusz (Computer Assisted Methods in Engineering and Science, 1997)
Optimization of shape and size of foundation should consider the type of loading, numerous geotechnical and geological parameters as well as various safety and economic criteria. Dimensioning depends on various, often controversial, conditions and involves many uncertainties. Therefore we search compromise solutions using nondeterministic analysis based on mathematical logic. In our solution we use computer simulations and results of reliability theory.